Description of Blood Pressure and Healthy Lifestyle Behavior among Employees - Glena Dwi Maharani; Aan Nur'aeni; Dadang Purnama (GLOBAL HEALTH SCIENCE GROUP, 2024)
Productive age workers often experience hypertension due to unhealthy lifestyles. Hypertension is known as